Ministry of Trade And Industry Decree No. 283 of the Year 2023 Amending Certain Provisions of the Statute of Rules Enforcing the Provisions of Law no. 118 of the year 1975 On Import and Export and the System of Imported and Exported Goods Inspection and Control Procedures = وزارة التجارة والصناعة قرار رقم 283 لسنة 2023 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام القانون رقم 118 لسنة 1975 فى شأن الاستيراد والتصدير ونظام إجراءات فحص ورقابة السلع المستوردة والتصدير - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic